Collective influence of 1-decanol addition, injection pressure and EGR on diesel engine characteristics fueled with diesel/LDPE oil blends. (1st October 2020) - Rajasekaran, S.; Damodharan, D.; Gopal, K.; Rajesh Kumar, B.; De Poures, Melvin Victor
Highlights: A blend of recycled fuel and renewable fuel was utilized in diesel engine. Collective influence of 1-decanol, fuel injection pressure and EGR on engine characteristics were studied. Best operating parameters were determined. Abstract: Plastic waste is abundant and its recovery to diesel-like fuel could reduce fossil fuel dependency and the associated risk of environmental pollution. In the present work, diesel-like fuel was produced from low-density polyethylene by catalytic pyrolysis method. Experiments were conducted to study the effect of substituting 10% vol. of 1-decanol in place of waste LDPE oil in D70L30 blend, under the influence of three injection pressures (400 bar, 500 bar, and 600 bar) and three EGR rates (0%, 10%, and 20%) on performance, combustion and emission characteristics of a CRDi engine at its rated power output. For this purpose, a ternary blend was prepared and the results were compared with diesel and D70L30 blend. Results reveal that, the substitution of 1-decanol in place of waste LDPE oil resulted in the shorter ignition delay period. The peak in-cylinder pressure and peak HRR dropped with increasing EGR rate and decreasing injection pressure. D70L20DEC10 injected at 600 bar with 0% and 10% EGR rates delivered 1.02% and 0.5% better BTE than D70L30 blend. NOx decreased by 112% when the EGR was increased from 0% to 20% at 400 bar FIP. It is concluded that the 1-decanol blend injected at 600 bar pressure and a low EGR rate of 10% gave the best possible performance and low emissions.